Immunity Activation in Brain Cells in Epilepsy: Mechanistic Insights and Pathological Consequences - Ravizza, Teresa; Kostoula, Chrysaugi; Vezzani, Annamaria (Neuropediatrics, 2013)
The search of targets for developing novel drugs that can control seizures resistant to available treatments in children and adults represents a great challenge for basic science. In the past decade, emerging evidence pointed out to the crucial role played by glia, the innate immunity brain-resident cells, in the generation of hyperexcitable neuronal networks underlying seizures. Molecular and pharmacological studies targeting glia, and the inflammatory mediators released by these cells in experimental models of epilepsy, highlighted novel targets for drug intervention aimed at interfering with the disease mechanisms, therefore providing putative disease-modifying treatments. This article will focus on the role of immunity activation in the brain and the concomitant release by glia of inflammatory molecules with neuromodulatory properties, in the pathogenesis of epileptic seizures, cell loss, and comorbidities.
Keywords: inflammation; glia; epilepsy